Optimal Cardiac Resynchronization Therapy Pacing Rate in Non-Ischemic Heart Failure Patients: A Randomized Crossover Pilot Trial. - Adam Ali Ghotbi; Mikael Sander; Lars Køber; Berit Th Philbert; Finn Gustafsson; Christoffer Hagemann; Andreas Kjær; Peter K Jacobsen (PLoS ONE, 2015)
The optimal pacing rate during cardiac resynchronization therapy (CRT) is unknown. Therefore, we investigated the impact of changing basal pacing frequencies on autonomic nerve function, cardiopulmonary exercise capacity and self-perceived quality of life (QoL).Twelve CRT patients with non-ischemic heart failure (NYHA class II-III) were enrolled in a randomized, double-blind, crossover trial, in which the basal pacing rate was set at DDD-60 and DDD-80 for 3 months (DDD-R for 2 patients). At baseline, 3 months and 6 months, we assessed sympathetic nerve activity by microneurography (MSNA), peak oxygen consumption (pVO2), N-terminal pro-brain natriuretic peptide (p-NT-proBNP), echocardiography and QoL.DDD-80 pacing for 3 months increased the mean heart rate from 77.3 to 86.1 (p = 0.001) and reduced sympathetic activity compared to DDD-60 (51±14 bursts/100 cardiac cycles vs. 64±14 bursts/100 cardiac cycles, p<0.05). The mean pVO2 increased non-significantly from 15.6±6 mL/min/kg during DDD-60 to 16.7±6 mL/min/kg during DDD-80, and p-NT-proBNP remained unchanged. The QoL score indicated that DDD-60 was better tolerated.In CRT patients with non-ischemic heart failure, 3 months of DDD-80 pacing decreased sympathetic outflow (burst incidence only) compared to DDD-60 pacing. However, Qol scores were better during the lower pacing rate. Further and larger scale investigations are indicated.ClinicalTrials.gov NCT02258061.